Three-Level Neutral Point Clamped Inverter Fed By A Photovoltaic System Under Partial Shading - Andrade, Abinadabe S.; Silva, Edison R. C. da (Eletrônica de Potência, 2016)
This paper deals with a system composed of a three-level Neutral-Point- Clamped inverter fed by photovoltaic panels. The system is able to operate adequately even under partial shading operation by controlling the dc-link neutral point injected current. System model, pulse width modulation strategy, maximum power point tracking, and control logic for balancing the dc-link capacitors voltages are presented. Analysis of harmonic distortion, thermal stress, limits of control and power losses are included. Experimental results validate the proposed system.